2021
DOI: 10.1242/dev.197566
|View full text |Cite
|
Sign up to set email alerts
|

Precision of tissue patterning is controlled by dynamical properties of gene regulatory networks

Abstract: During development, gene regulatory networks allocate cell fates by partitioning tissues into spatially organised domains of gene expression. How the sharp boundaries that delineate these gene expression patterns arise, despite the stochasticity associated with gene regulation, is poorly understood. We show, in the vertebrate neural tube, using perturbations of coding and regulatory regions, that the structure of the regulatory network contributes to boundary precision. This is achieved, not by reducing noise … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 81 publications
(158 reference statements)
1
44
0
Order By: Relevance
“…For example, the authors of [ 39 ] classified the qualitative behaviors of attractors and trajectories in toggle switches with time-dependent (morphogen) inputs and subsequently used these classifications to describe the dynamic behavior of the gap gene network in fruit flies [ 15 ]. Similarly, the authors of [ 29 ] found that stochastic gene expression could result in boundary refinement over specific timescales, and confirmed the effect experimentally in a larger network [ 27 ]. Such approaches leverage a thorough understanding of simple models to make sense of more complex cases, enabling researchers to generate new insights, predictions, and perspectives along the way.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…For example, the authors of [ 39 ] classified the qualitative behaviors of attractors and trajectories in toggle switches with time-dependent (morphogen) inputs and subsequently used these classifications to describe the dynamic behavior of the gap gene network in fruit flies [ 15 ]. Similarly, the authors of [ 29 ] found that stochastic gene expression could result in boundary refinement over specific timescales, and confirmed the effect experimentally in a larger network [ 27 ]. Such approaches leverage a thorough understanding of simple models to make sense of more complex cases, enabling researchers to generate new insights, predictions, and perspectives along the way.…”
Section: Introductionsupporting
confidence: 52%
“…Determining whether a model accurately captures an empirical behavior requires systematic and often quantitative comparison of theoretical predictions with experimental results. For example, the mathematical effect observed in [ 29 ] to refine gene expression boundaries in stochastic models was empirically verified in vertebrate neural tube through a careful interplay of theory and experiment [ 27 ]. We encourage the community to follow the example of these authors in future efforts to validate a proposed model, or to differentiate among potentially many mathematical descriptions of the same phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For spatial signals, binding with membrane-bound non-signaling entities [25], regulation of gradient steepness by ligand shuttling [26,27] and self-regulated ligand uptake [28,29] can reduce spatial variation in morphogen gradients. Anti-parallel morphogens [14] and gene regulatory networks [30][31][32] that translate noisy spatial signals into cell fate decisions can also reduce patterning errors. Interestingly, noise in gene expression can counteract other stochastic effects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Downstream of extrinsic signaling, progenitor cells employ gene regulatory networks (GRNs) to interpret morphogen gradients and regulate cell fate 16 . During neural tube development, Otx2 is expressed in anterior regions, whereas Gbx2 is expressed in posterior regions at early stages of development.…”
Section: Introductionmentioning
confidence: 99%